Development of Animated Learning Media for the Pancasila Education Subject in Grade III Elementary School - Sovia Astari; Ulfia Rahmi; Yeni Erita; Desri Nora AN (Journal of Educational Sciences, 2026)
This study was motivated by the limited teacher innovation in using learning media, where lectures and printed textbooks still dominate classroom activities, making it difficult for students to grasp abstract concepts. Therefore ,animated learning media was developed to enhance student comprehension, participation, and achievement in Pancasila Education for third grade elementary students. The research used a Research and Development (R&D) approach with the ADDIE model, consisting of five stages, Design, Development, Implementation, and Evaluation stages. The subjects were Grade III  students at SD Negeri 19 Air Tawar Barat and SD Negeri 52 Parupuk Tabing. Data collection instruments included expert validation sheets, practicality questionnaires, and effectiveness tests, with analysis focusing on validity, practicality, and effectiveness. Results showed that the developed media achieved very valid scores from material experts (95%), media experts (91.25%), and language experts (100%). Practicality tests revealed positive responses from teachers (96.67%) and students (95.38%). Effectiveness was confirmed by an N-Gain score of 0.81, with average student scores rising from 59.72 (pretest) to 91.84 (posttest). In conclusion, the animated learning media was proven valid, practical, and effective, providing an engaging tool that supports a more interactive and meaningful learning process in Pancasila Education for elementary schools.